The Influence of Islamic Insurance And Islamic Banks on Indonesia's Economic Growth For The Period 2016-2022 - Batubara, Maryam; Andiyanto, Sakti (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Purpose: The goal of this research is to discover and assess the impact of Islamic insurance and Islamic banks on economic growth. Examining the Impact of Islamic Insurance on Indonesian Economic Growth and the Impact of Islamic Banks on Indonesian Economic Growth. In this scenario, the research was carried out between 2016 and 2022.Design/Method/Approach: This is descriptive study using a quantitative research technique. With secondary data sources obtained from financial reports published by the Financial Services Authority (OJK), namely IKNB Sariah which contains financial reports for all sharia insurance and banking statistics for the 2016-2022 period. In this research, the population and sample are all monthly financial reports of Indonesian Sharia Insurance and sharia banking in quarterly form for the period 2016-2022. Economic growth is the research's dependent variable. Meanwhile, Sharia Insurance and Sharia Banking are the independent factors. This study's data will be examined utilizing research instrument testing, traditional assumption tests, multiple regression tests, and hypothesis tests.Findings: According to the partial test results, the Islamic insurance variable has no significant influence on economic growth in Indonesia for the 2016-2022 periods; however the Islamic banking variable has a positive and substantial effect on economic growth in Indonesia for the 2016-2022 periods. While the test findings between Islamic Insurance and Islamic Banks on Indonesian Economic Growth, the two data evaluated in this study combined have a substantial impact on economic growth.Originality/Value: This study adds value by examining the impact of Islamic Insurance and Islamic Banks to annual economic development in Indonesia from 2016 to 2022. Also as a fundamental study to see the opportunities and weaknesses of Islamic Insurance and Syraiah Banking in Indonesia, for Indonesia's economic growth.